Perbandingan Direction Ascending dan Descending di Segmen Sianok Sesar Semangko Menggunakan Metode Ps-InSAR - Monalisa Perwanda; Dwi Marsiska Driptufany; Sayidinal Fikri; Dwi Arini; Fajrin Fajrin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The movement of the Sumatran fault is triggered by plate activity in the western subduction zone of Sumatra, namely the Indo-Australian plate which moves down the Eurasian plate, causing pressure to push the Sumatra region towards the north. The purpose of this study is for the results of Ascending and Descending data on the impact of faults that occur on the Semangko Segment Sianok fault from 2020-2023 and to map the Land Displacement of the Semangko Segment Sianok fault from 2020-2023. Based on the results of data processing in this study, it can be concluded that in this study using ascending and descending direction data that experienced land movement (Land Displacement) due to this movement the impact of faults that occurred due to seismic activity along the segment resulted in the impact of natural disasters such as landslides, and earthquakes. This impact was triggered due to land movement because the effects of surface faults and ground shaking did cause most of the damage in several events. The ascending data explains the annual uplift of 15.28 mm marked in dark blue and the red color on the map shows the subsidence of -30.55 mm per year, while the light bitu color dominates in urban areas or areas inhabited by many people. While in the descending data, changes in land movement show an annual uplift of 6.74 mm and the red color shows subsidence of -13.47 mm per year. From the color change of each data shows ascending and descending data experiencing land subsidence uplift and subsidence.